APPLYING COOPERATIVE LEARNING FOR SPEECH CLASS AT THE SECOND SEMESTER STUDENTS OF STMIK ATMA LUHUR PANGKALPINANG - S, SINTA (English Community Journal, 2020)
”The problems of this study:“Is cooperative learning effectively used in teaching English for  Speech to the Second Semester Students of STMIK ATMAL UHUR PANGKALPINANG?” The method of research used in this study was the experimental research. The type of experimental method used was quasi-experimental. The result of the test was analyzed by using SPSS Program. Based on the result  of the data analysis, From the scores that were found, the result of statistical analysis between experimental and control group (t-obtained) should be higher than t-table (0.05) for two tailed. Furthermore the result of the students’ score in control and experimental group (value of t-obtained) was -10.325. Since the value of t-obtained was higher than t-table, so that the null hypothesis was rejected and alternative hypothesis was accepted. It can be stated that teaching English for Speech using dialoq with cooperative learning method is more effective than conventional way to the second semester students at STMIK ATMA LUHUR PANGKALPINANG.